Revolution of Piercing the Corporate Veil Doctrine In England: A Common Law Perspective On VTB Capital v. Nutritek - Angel, Vanessa; Tan, David; Afdal, Windi (Hang Tuah Law Journal, 2025)
The doctrine of piercing the corporate veil serves as a mechanism of justice and policy aimed at protecting third parties from the actions of a company. This legal concept is applied in common law jurisdictions, including the UK, and is exemplified by the case of VTB Capital PLC v. NutritekInternational Corp. This research aims to analyze the developmental stages of the doctrine of piercing the corporate veil, particularly in the UK and in the context of VTB Capital PLC v. Nutritek International Corp. The methodology employed in this study is normative juridical research. The results indicate that shareholder liability is generally limited to their capital contribution; however, the doctrine of piercing the corporate veil can be applied if a legitimate shareholder uses the company for illegal purposes, particularly in cases where there are indications of fraud. Additionally, the court possesses common law jurisdiction to lift the corporate veil, but this authority is typically exercised only under special circumstances. Justice ought to serve as a guiding principle, though it may sometimes appear obscured by the complexities involved in attempts to penetrate the corporate veil. Such attempts, whether initiated by the plaintiff or the defendant, reveal the challenges of balancing corporate protections with accountability. The application of the Piercing the Corporate Veil (PCV) doctrine can be evaluated from multiple perspectivesboth in terms of its legal basis or more into common way.